European chemicals regulation and its effect on innovation: An assessment of the EU's White Paper on the strategy for a future chemicals policy - Ralf Nordbeck; Michael Faust (UFZ-Umweltforschungszentrum Leipzig-Halle, 2002)
In February 2001, the European Commission published its White Paper on a Strategy for a Future Chemicals Policy. The publication launched a heated debate on principles, aims, instruments, implementation, and management of future chemicals control in the European Communities. The White Paper came in wake of massive criticism of current chemicals legislation. Various parties involved repeatedly expressed their concern about a tremendous lack of effectiveness. Furthermore, comparisons with other industrialized countries outside the EU indicated that the current regulatory framework actually discourages innovation in the European chemicals industry. This paper examines current European chemicals policy and main elements of the White Paper strategy with a special focus on the impact of chemicals regulation on innovation towards sustainability. The claim that chemicals regulation tends to block innovation is rejected for lack of conclusive proofs. In contrast, the paper reinforces the view that the White paper strategy is an important step forward towards sustainability in the chemicals sector. However, with the aim to make it pay for companies to pursue environmentally orientated innovation strategies, supporting measures and instruments need to be developed further.
Keywords: 330; Chemikalienrecht; Reform; EU-Umweltrecht; Innovation; Chemieindustrie; Nachhaltige Entwicklung; EU-Staaten